Pricing Model of Palm Oil by Toke: An Islamic Economic Perspective on Indebted Farmers - Rima; Musthofa , M. Arif; Yatima, Khusnul; Daud; Sarwono; Wulandari, Triyana; Edi Saputra, Ahmad (Journal of Economics and Social Sciences (JESS), 2025)
This study examines the unilateral price-setting practices by toke (middlemen) on indebted palm oil farmers in Muara Sabak Timur District from an Islamic economic perspective. The findings reveal that price determination occurs without farmers’ consultation or mutual consent, leading to significantly lower prices for indebted farmers compared to debt-free counterparts. This practice exacerbates economic injustice and deepens farmers’ dependency on toke, who use debt as a covert mechanism of price control. The study identifies elements of gharar (uncertainty), zulm (oppression), and ikrah (coercion) in the pricing practices, which violate the Islamic principle of an-tarāḍin (mutual consent) in transactions. Recommendations include establishing Sharia-compliant cooperatives and microfinance institutions offering interest-free financing and transparent, fair pricing mechanisms. Additionally, the study proposes the implementation of hisbah supervision as a social control instrument to prevent exploitative practices. The research contributes to the agrarian economic literature by integrating maqāṣid shariah principles to promote social justice and economic empowerment for small-scale farmers, ultimately supporting sustainable development and equitable market systems